Nomenclatural emendations of the family-group names Cylindrolepadinae, Stomatolepadinae, Chelolepadinae, Cryptolepadinae, and Tubicinellinae of Ross & Frick, 2007—including current definitions of family-groups within the Coronuloidea (Cirripedia: Balanomorpha) - Ross, Arnold; Frick, Michael F. (Zootaxa, 2011)
The coronuloid barnacle family-group names Cylindrolepadinae, Stomatolepadinae, Chelolepadinae, Cryptolepadinae and Tubicinellinae of Ross & Frick, 2007 are considered nomen nudum according to Article 8.6 of the International Code of Zoological Nomenclature, but appear in several subsequent published works and internet taxonomic databases. It is the purpose of this communication to rectify this situation. These five subfamilial names are proposed and defined herein anew, as Cylindrolepadinae subfam. nov., Stomatolepadinae subfam. nov., Chelolepadinae subfam. nov., Cryptolepadinae subfam. nov. and Tubicinellinae subfam. nov. The remaining valid family-group names within the Coronuloidea are also listed and defined herein.